Multidimensional Change Management Strategies of School Superintendents in Strengthening Standards Process in Post-Covid-19 Era: A Phenomenological Study in Ponorogo - Yahya, Fata Asyrofi; Hariyanto, Wahid (EDUKASIA, 2025)
This study aims to explore the efforts of school superintendents in managing the changes caused by the Covid-19 pandemic, which has led to a decline in the quality of process standards in schools, and to measure the results. Examining the issue of declining the quality of process standard by using change management strategy has not been conducted in earlier studies. This research used a qualitative approach with a phenomenological type. This research took place at elementary school in Ponorogo. The informants in this research consisted of school superintendents who are members of Ponorogo Branch of the Indonesian School Supervisors Association (APSI) as well as principals of elementary schools in Ponorogo. The results of this research revealed that: first, school supervisors have managed the changes that occur in their target schools through ADKAR steps combined with technology, namely: awareness, desire, knowledge, ability and reinforcement which are supported by using information technology. Second, the success of change management in improving the quality of process standards could be divided into three points, namely improvement, stagnation and decline.